Effects of Automated Manufacturing System Towards Workforce’s Behaviours - S. T., Syed Shazali; M. S., Osman; H. M., Johan; A., Yassin; M. I., Shahidul; M., Andrew-Munot; M. A., Mohd Said (ENCON 2013, 2013)
Regardless how advanced the manufacturing system is in this current global era, workforces are still the number one element in manufacturing industry. In view of this, this research attempts to discover the effects of automated manufacturing system on the worker’s behaviours by concerning on the shop floor workers and work attitudes. This psychological effect of study is particularly focusing on the relation between the implementation of automated manufacturing system in Small Medium Enterprises (SMEs) in the local area specifically in Kuching. They are based on social interaction, product demand, quality outcomes, system performance and how these behavioural and non-behavioural variables affect the accomplishment in terms of performance and job awareness of the workforces. Behaviours will be shown automatically when a person is taking or doing an action. These behaviours will somehow affect not only the quantity of the product produced but as well as they affect the quality of the product. The relationship of man-machine interaction does give an impact to the productivity of the company. This study discovered that the effect of integrated system leads to higher mental workload and fatigue.